Visible‐near‐infrared reflectance spectroscopy of volcanic acid‐sulfate alteration in Nicaragua: Analogs for early Mars. Issue 10 (22nd October 2013) - Marcucci, Emma C.; Hynek, Brian M.; Kierein‐Young, Kathryn S.; Rogers, K. L.
<x xml:space="preserve">Abstract</x> [1] Acid‐sulfate weathering at Nicaraguan hydrothermal sites Cerro Negro, Momotombo, and Telica volcanoes and Hervidores de San Jacinto mudpots was characterized as an analog for similar processes that likely operated on early Mars. In situ mineralogical analyses were conducted with a field portable visible near‐infrared spectrometer for comparison to similar Martian data sets. Three classes of alteration minerals were identified: sulfates (gypsum and natroalunite), oxides/hydroxides (hematite and goethite), and phyllosilicates (kaolinite/halloysite, montmorillonite, and saponite), as well as elemental sulfur and hydrated silica phases. Our sites had similar suites of minerals, but frequencies varied with location. The results of this field campaign allow inferences regarding the paleo‐environmental conditions that were likely present at similar relic hydrothermal sites identified on Mars. In particular, sulfates and phyllosilicates could have coevolved under hydrothermal conditions at Noctis Labyrinthus as is seen in Nicaragua. Fe/Mg smectites were detected in areas with pH of 3–4. Alunite spectra at Terra Sirenum demonstrated mineral mixing effects on spectroscopy. Mineral mixing can cause uncertainties in spectral identification due to a dominant spectrum, such as iron minerals, masking another or the suppression of weaker bands. When viewed from orbit, our field sites would likely be dominated by hydrated silica and Mars sites, such as one in Syrtis Major, could have a more diverse mineralogy than the data reveal. Concentrated amorphous silica, such as at Gusev crater, can result from acidic fumarolic activity, while Mg sulfates may indicate a lack of reworking by water. This field spectroscopy study helps confirm and provide insight into hydrothermal processes on ancient Mars.